Enzymatic sialylation of IgA1 O-glycans: implications for studies of IgA nephropathy - Takahashi, Kazuo; Raska, Milan; Stuchlova Horynova, Milada; Hall, Stacy D; Poulsen, Knud; Kilian, Mogens; Hiki, Yoshiyuki; Yuzawa, Yukio; Moldoveanu, Zina; Julian, Bruce A; Renfrow, Matthew B; Novak, Jan (PloS one, 2014)
Patients with IgA nephropathy (IgAN) have elevated circulating levels of IgA1 with some O-glycans consisting of galactose (Gal)-deficient N-acetylgalactosamine (GalNAc) with or without N-acetylneuraminic acid (NeuAc). We have analyzed O-glycosylation heterogeneity of naturally asialo-IgA1 (Ale) myeloma protein that mimics Gal-deficient IgA1 (Gd-IgA1) of patients with IgAN, except that IgA1 O-glycans of IgAN patients are frequently sialylated. Specifically, serum IgA1 of healthy controls has more α2,3-sialylated O-glycans (NeuAc attached to Gal) than α2,6-sialylated O-glycans (NeuAc attached to GalNAc). As IgA1-producing cells from IgAN patients have an increased activity of α2,6-sialyltransferase (ST6GalNAc), we hypothesize that such activity may promote premature sialylation of GalNAc and, thus, production of Gd-IgA1, as sialylation of GalNAc prevents subsequent Gal attachment. Distribution of NeuAc in IgA1 O-glycans may play an important role in the pathogenesis of IgAN. To better understand biological functions of NeuAc in IgA1, we established protocols for enzymatic sialylation leading to α2,3- or α2,6-sialylation of IgA1 O-glycans. Sialylation of Gal-deficient asialo-IgA1 (Ale) myeloma protein by an ST6GalNAc enzyme generated sialylated IgA1 that mimics the Gal-deficient IgA1 glycoforms in patients with IgAN, characterized by α2,6-sialylated Gal-deficient GalNAc. In contrast, sialylation of the same myeloma protein by an α2,3-sialyltransferase yielded IgA1 typical for healthy controls, characterized by α2,3-sialylated Gal. The GalNAc-specific lectin from Helix aspersa (HAA) is used to measure levels of Gd-IgA1. We assessed HAA binding to IgA1 sialylated at Gal or GalNAc. As expected, α2,6-sialylation of IgA1 markedly decreased reactivity with HAA. Notably, α2,3-sialylation also decreased reactivity with HAA. Neuraminidase treatment recovered the original HAA reactivity in both instances. These results suggest that binding of a GalNAc-specific lectin is modulated by sialylation of GalNAc as well as Gal in the clustered IgA1 O-glycans. Thus, enzymatic sialylation offers a useful model to test the role of NeuAc in reactivities of the clustered O-glycans with lectins.
Keywords: lektiny; Recombinant Proteins; sacharidové sekvence; HEK293 buňky; kyseliny sialové; Helix (hlemýždi); molekulární sekvence - údaje; Amino Acid Sequence; HEK293 Cells; Sialic Acids; IgA nefropatie; glykosyltransferasy; polysacharidy; rekombinantní proteiny; Animals; lidé; Lectins; Humans; zvířata; sekvence aminokyselin; imunoglobulin A; Carbohydrate Sequence; Glycosyltransferases; Molecular Sequence Data; Polysaccharides; Helix, Snails; Immunoglobulin A; Glomerulonephritis, IGA